Numerical Simulation during Short-Shot Water-Assisted Injection Molding Based on the Overflow Cavity for Short-Glass Fiber-Reinforced Polypropylene - Zhong Yu; He-Sheng Liu; Tang-Qing Kuang; Xing-Yuan Huang; Wei Zhang; Zhong-Shi Chen; Kai Zhang (Advances in Polymer Technology)
Compared with water penetration condition of short-shot water-assisted injection molding with or without overflow cavity, it can be known from theory and common knowledge that short-shot water-assisted injection molding with overflow cavity has many advantages, such as it can save materials and energy. Then, the effects of melt short shot size, water injection delay time, melt temperature and water injection pressure on the penetration of water after penetration, and the orientation distribution of short fibers during water-assisted injection molding of the overflow cavity short-shot method were studied. It is found that the melt short shot size had the greatest influence on it, followed by water injection pressure, water injection delay time, and finally, melt temperature. With the increase of the melt short shot size, the thickness of the residual wall of the whole main cavity becomes thinner, the orientation of short fiber along the melt flow direction becomes higher, and the degree of fiber orientation changes becomes lower. In the front half of the main cavity, with the decrease of water injection pressure, the delay time of water injection, and the melt temperature, in the front part of the main cavity, the residual wall thickness becomes thinner, the fiber orientation along the melt flow direction becomes lower, and the fiber orientation changes degree becomes higher; in the latter half of the main cavity, the influence of the water penetration and the orientation distribution of short fibers along the melt flow direction are not significant.